EUV Radiation in the Range of 10–20 nm from Liquid Spray Targets Containing O, Cl, Br and I Atoms under Pulsed Laser Excitation - Valerie E. Guseva; Andrey N. Nechay; Alexander A. Perekalov; Nicolay I. Chkhalo (Photonics, 2024)
The article describes the results of an investigation to determine the values of radiation intensities emitted by O-, Cl-, Br-, and I-containing liquid spray targets in absolute units in the wavelength range 10–20 nm when excited by pulsed laser radiation. The conversion coefficients of laser radiation into the EUV radiation are given for some wavelengths. The authors’ specially designed pulse extrusion liquid supply system was used to form the liquid spray targets. An Nd:YAG laser with λ = 1064 nm, τ = 8.4 ns, and Epulse = 0.8 J was used to excite the targets. Spectral measurements were made using a grazing incidence grating spectrometer–monochromator. The absolute intensities of a number of emission lines were also measured using a Bragg spectrometer based on a Mo/Be multilayer X-ray mirror, calibrated by both sensitivity and wavelength. The high values of absolute intensities of the liquid targets in the extreme ultraviolet wavelength range were demonstrated.